Practical Applications of a Vision-based Robot for Security and Safety of Tailings Tunnels Infrastructure in the Mining Industry - Ramirez, J.; Segovia, A.; Escobar, M.; Quiroz, D.; Cuellar, F. (Institute of Electrical and Electronics Engineers, 2021)
In the mining industry, inspection of water recovery tunnels from tailings ponds is a critical activity in order to prevent disasters that could harm personnel, the environment and the infrastructure. Tunnel inspections are considered of high risk due to hazardous conditions such as working near water sources, inside confined spaces and the presence of toxic gases. We propose the use of a vision-based robotic vehicle for water recovery tunnels inspection, improving the security and safety of this high risk but required task. This paper describesthe experience of performing a remote inspection of a tailing pond water recovery tunnel using a robot. The identification of challenges, the establishment of a inspection plan, the remote inspection methodology and the safety regulations required in the mining industry are detailed. After evaluating the performance of the inspection robot in field, the need for a 3D reconstruction functionality in order to improve the tunnel diagnosis was identified. The design, preliminary test and results of the performance of a 3D reconstruction module for the inspection robot are presented and discussed.
Keywords: Hazardous waste; Tailings; Robot; Plan (archaeology); Harm; Mining industry; Task (project management); Engineering; Computer science; Construction engineering; Risk analysis (engineering); Mining engineering; Systems engineering; Artificial intelligence; Business; Waste management; https://purl.org/pe-repo/ocde/ford#2.07.05